Guided-Mode Resonant <tex Notation="TeX">$\hbox{HfO}_{2}$</tex> Grating at Visible Wavelength Range - Yongjin Wang; Xumin Gao; Zheng Shi; Lifeng Chen; Martin Lopez Garcia; Nikolai A. Hueting; Martin Cryan; Xin Li; Miao Zhang; Hongbo Zhu (IEEE Photonics Journal, 2014)
Subwavelength HfO2 gratings are realized on a freestanding 200-nm-thick HfO2 membrane with air as the low refractive index materials on top and bottom. Strong coupling between the incident light and HfO2 grating is characterized by angular-resolved reflectivity measurement, and guided-mode resonances are experimentally demonstrated with the sensitivities to the parameters and shapes of grating and the polarization of incident beam. The experimental results are consistent with numerical simulation. This work opens the way to fabricate guided-mode resonant HfO2 photonic devices in the visible wavelength range.